Fundamentos do conceito do amor-ágape como causalidade eficiente na metafísica de C. S. Peirce - Simões, Bárbara Beatriz Silvestre Sampaio (2022)
This master's dissertation has as its object of study the theory formulated by Charles Sanders Peirce about agapasma, presented in his essay Evolutionary Love, where the philosopher claims that agape is a “directing” cosmic force that guides evolution towards its telos. Thus, this dissertation proposes to investigate the theoretical foundations that led Peirce to conceive agapastic evolution as the only evolutionary model adequate to the telos of evolution, based on the way of articulating the concepts of chance and necessity. To this end, the architectural exposition of Peirce's Metaphysics is essential, in order to avoid any misinterpretation of Peirce as a mystic; on the contrary, Peirce's Metaphysics is based on logical principles and, therefore, is conceived as a Scientific Metaphysics. Finally, based on Aristotle's concepts of causes, this dissertation seeks to demonstrate how agape-love can be interpreted as an efficient cause responsible for the movement of passage from potency to act, in a world in continuous evolution